Atypical features of a Ure2p glutathione transferase from Phanerochaete chrysosporium. Issue 14 (24th May 2013) - Thuillier, Anne; Roret, Thomas; Favier, Frédérique; Gelhaye, Eric; Jacquot, Jean-Pierre; Didierjean, Claude; Morel-Rouhier, Mélanie
Abstract : Glutathione transferases (GSTs) are known to transfer glutathione onto small hydrophobic molecules in detoxification reactions. The GST Ure2pB1 from Phanerochaete chrysosporium exhibits atypical features, i.e. the presence of two glutathione binding sites and a high affinity towards oxidized glutathione. Moreover, PcUre2pB1 is able to efficiently deglutathionylate GS‐phenacylacetophenone. Catalysis is not mediated by the cysteines of the protein but rather by the one of glutathione and an asparagine residue plays a key role in glutathione stabilization. Interestingly PcUre2pB1 interacts in vitro with a GST of the omega class. These properties are discussed in the physiological context of wood degrading fungi. Abstract : PcUre2pB1 reduces both insulin and glutathionylated‐PcGSTO3. The holodimeric enzyme binds one molecule of oxidized glutathione per monomer. Catalysis is not mediated by the cysteines of the protein but rather by the one of glutathione. An asparagine residue is involved in glutathione stabilization.